Preventing the spread of H1N1 influenza infection during a pandemic: autonomy-supportive advice versus controlling instruction - Chan, Derwin; Yang, Sophie Xin; Mullan, Barbara; Du, X.; Zhang, X.; Chatzisarantis, Nikos; Hagger, Martin (Springer New York LLC, 2015)
Wearing facemask is an effective strategy for preventing the spread of the H1N1 in enclosed public spaces. This quasi-experiment examined the effects of University professor ‘autonomy support on students’ motivation, social cognitive factors, and intention to wear facemasks in the lecture hall during a hypothetical H1N1 pandemic. University students (N = 705) completed self-report measures of motivation, social cognitive factors, and intention according to a hypothetical H1N1 pandemic scenario in which their professors asked them to wear facemasks in the lecture hall, using either an ‘autonomy-supportive’ interpersonal style or a ‘controlling’ style. The results showed that the manipulation of professors’ autonomy support exerted a positive effect on students’ perception of autonomy support, which positively predicted their self-determined motivation, social cognitive factors, and intentions to wear facemasks. In conclusion, promoting self-determined motivation using autonomy-supportive communication styles might be an effective means of fostering individuals’ adaptive beliefs and motivation of H1N1 prevention.